The Implementation of Differentiated Learning in Merdeka Curriculum In Learning English at High School - Sri Wahyuni (Universitas PGRI Adi Buana Surabaya, 2023)
An independent curriculum is a policy of learning program designed to restore the national education system. It enables schools, teachers, students, and all school resources to innovate, be creative, and learn independently. Teachers are the main drivers in this process. In differential learning, teachers choose the material to be taught taking into account students' readiness, interests, and learning styles. Currently, educators are more inclined to use conventional learning approaches. In this case, a teacher-center learning approach is used rather than a student-centric learning approach. The aim of this study is to find out how differential learning is used in an independent curriculum for English courses in high school (SMA). The study uses qualitative descriptive methods. The results of this study show that differential learning can be applied in an independent curriculum to English subject.